Education on a Clean and Healthy Lifestyle as an Effort to Prevent Covid-19 - Hanum, T. Ismanelly; Sumaiyah; Maha, Hetty Lendora; Purba, Djendakita (Talenta Publisher, 2021)
Binjai sub-district is located in the Â Medan Denai district, has a relatively dense residential area. The interaction between communities is very intense, potentially spreading disease transmission, especially the current pandemic, Coronavirus disease 2019 (COVID-19). This situation is quite worrying because many people are positive for COVID-19, and some suspects have died. Public awareness in preventing COVID-19 infectious diseases such as physical distancing and washing hands is still lacking. Therefore, this activity aimed to educate the public to increase awareness through a clean and healthy lifestyle movement. Activities carried out using extension methods, demonstrations, and discussions. The activity participant accepted a pre-test and post-test, brochures, and education about the dangers of the contagious disease COVID-19 and its prevention, including its application to a clean and healthy lifestyle. Partners also practiced proper handwashing using soap and hand sanitizer. The pre-test and post-test showed that from the 21 participants who attended, the participants' knowledge increased by 70%. Educational activities in this activity are critical because a healthy and clean lifestyle is a manifestation of healthy living in the culture of individuals, families, and communities, which aims to improve, maintain and protect their health both physically and mentally, spiritual, and social.